(untitled) (Journal of the College of Basic Education, 2022)
Egypt is the first country in contemporary history in which the movements of political Islam thought emerged, and the apparent goal of its establishment was to unify Muslims, restore the Islamic renaissance and rid the Islamic world of foreign colonialism, and therefore these ideas were found acceptable by some Muslim youth and were the first movements that adopted the thought Political Islam is the Muslim Brotherhood movement founded by Sheikh Hassan Al-Banna in 1928, and most of the political Islam parties, movements, and groups in the Islamic world emerged from under its cloak. We focused in our study on one of those groups that are considered the most extreme and dangerous, which is the Muslim group or what is known as the group of infidelity and migration, and our choice of this topic came to reveal the truth of those groups that legalized terrorism, and intimidation as a deviant ideology and took it as a method for their work, and that they are subversive movements that try to destroy The Islamic community and its return to the backward, stopping the process of progress and development and distorting the image of Islam as a religion of tolerance and coexistence with religions, and other societies, as well as those terrorist organizations exerted the Egyptian state in terms of security and its threat to the civil peace of society and broadcast ideas poisoning the ideas of youth.